2012
DOI: 10.1134/s1070363212050039
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoramidates: Features of the formation mechanism and the relationship structure-bioaction

Abstract: Mechanism of the synthesis of phosphoramidates by Todd-Atherton reaction is based on the primary interaction of a polyhaloalkane with the highly basic amine to form a 1:1 associate. The subsequent attack by the associate on the hydrophosphoryl compound of "symmetric" structure leads to the formation of the target compounds in high yields. The test of the effect of dialkyl hexamethylene-and dialkyl(pyridin-2-yl)-phosphoramidates in vitro against the strains of a number of the producents of pathogenic bacteria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…The MIC value for all the compounds was found to be >128 μM, indicating no antimicrobial activity (Table S1). The lack of antimicrobial activity can be correlated with structure‐activity relationship (SAR) [66] . It has been observed that only phosphoramidates with heterocycles and electron withdrawing groups (like −NO 2 , F) on the aromatic rings are capable inhibiting microbial growth [63–65] .…”
Section: Resultsmentioning
confidence: 99%
“…The MIC value for all the compounds was found to be >128 μM, indicating no antimicrobial activity (Table S1). The lack of antimicrobial activity can be correlated with structure‐activity relationship (SAR) [66] . It has been observed that only phosphoramidates with heterocycles and electron withdrawing groups (like −NO 2 , F) on the aromatic rings are capable inhibiting microbial growth [63–65] .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the use of UV irradiation or radical initiators in the absence of trialkylamine was found to be unsuccessful to produce phosphoramidates. Recently, Krutikov et al [ 9 ] have reported that hexahydroazepine (a secondary amine with a p K a of 11.1 ( Scheme 3 -iii), used as a base in the AT reaction) probably reacted first with carbontetrachloride to produce a charge-transfer complex (this type of interaction was confirmed by refractometric titration). However, in this reaction the trichloromethylphosphonate, which would result from the reaction of the anion CCl 3 − with chlorophosphate, was never observed because CCl 3 − probably reacted as a base in the presence of dialkylphosphite ( Scheme 3 -ii).…”
Section: Reviewmentioning
confidence: 96%
“… Two reaction pathways (i and ii) to produce chlorophosphate 2 . Charge-transfer complex observed when hexahydroazepine was used as a base (iii); adapted from [ 6 ] and [ 9 ]. …”
Section: Reviewmentioning
confidence: 99%
“…To the best of our knowledge, all hitherto known variants of the Atherton–Todd reaction are only realized in the presence of the oxidative system base/polyhaloalkane (as a rule, in the Et 3 N/CCl 4 system) . According to the latest data [c, ], the role of this system is in its interactions with dialkylphosphites by two pathways (i and ii) to produce intermediate chlorophosphate A (Scheme ).…”
Section: Introductionmentioning
confidence: 99%